Working capital and sustainability of private practices in the South African healthcare sector - Kondlo, Nangamso (University of the Witwatersrand, Johannesburg, 2023)
The major aim of this quantitative exploratory study was to investigate the impact that working capital has on the long-term sustainability of small businesses; focusing on private practices in the health sector. The study contributes towards an understanding of the role that working capital plays in improving the chances of survival and thriving for small and medium-sized businesses in South Africa. The study sample (n=76) was drawn from a population consisting of all general practitioners who run private practices in the Gauteng Province of South Africa. Data was collected through an online questionnaire administered via Survey Monkey. The questionnaire used had both closed and open-ended items. Answers to closed questionnaire items were analysed using descriptive statistics. The responses to open-ended items were analysed using content analysis, from which descriptive statistics were derived. The findings show that: private practices fund their working capital needs mainly through overdrafts and bank loans; there is a relationship between working capital and the sustainability of private practices; and the government and current policy frameworks are not doing enough to support the long-term sustainability of private practices in the health sector. Suggestions on how private practices can finance working capital requirements are given. It is recommended that amendments to public policy should be done, focusing on how to improve the long-term sustainability of private practices. Recommendations for future research are teased out
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: UCTD; Working capital; Long-term sustainability; Small businesses; Health sector; SDG-3: Good health and well-being